Formation of Small-Volumetric Livestock Buildings on the Principles of Cooperation and Blocking - Nesterenko, Svitlana; Koshlatyi, Oleg; Mishchenko, Roman; Shchepak, Vira (International Journal of Engineering and Technology, 2018)
The features of livestock buildings functional organization and planning were investigated, the factors forming the building for different livestock maintenance were established. Proposals and recommendations for the design of small-volumetric cattle-breeding cooperative and blocked buildings have been developed. The formation of new types and the nomenclature of livestock cooperative buildings with various types of animals, the pattern of possibility such buildings cooperation and blocking was proposed. The possibility of model objects formation, based on the main optimization criterions was found theoretically. The buildings arrangement planning modelling and determination have become possible to computerize due to compound algorithms for calculation of small-volumetric cattle-breeding building, block-schemes and developed functional and technological blocks.Â